(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Sometimes in free flap there is a venous congestion without an obstruction of the venous anastomosis or other organic causes of reduction venous drainage (hematoma, seroma compressing the pedicle). In these cases the authors suggest the application of nitroglycerine patch in the congested area of the flap few hours before the surgical exploration of the anastomosis . If there is a fast improvement of the clinical feature of the flap, the surgical exploration could be avoided. The authors underline that applying the nitroglycerin patch should not be regarded in any way as a therapy of a free flap venous thrombosis but only as an useful device, an option to be taken only when the surgeon is undecided whether to revisit the anastomosis or not.